2013
DOI: 10.1142/s2251171713400114
|View full text |Cite
|
Sign up to set email alerts
|

Phase-Referenced Interferometry and Narrow-Angle Astrometry With Susi

Abstract: This thesis describes the development of an astrometric facility at the Sydney University Stellar Interferometer (SUSI) with an aim to measure at high precision the relative astrometry of bright close binary stars and ultimately to detect the presence of exoplanets within those binary star systems through observations of the systems' perturbed motion. At the core of the facility is a new beam combiner that is phase-referenced to an existing primary beam combiner in the visible wavelength regime. The latter pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 95 publications
(166 reference statements)
0
4
0
2
Order By: Relevance
“…Celui-ci a été mis en oeuvre dans l'infrarouge (l'effet de la turbulence et la dispersion y étant moins intenses que dans le visible) au Palomar Testbed Interferometer (à trois télescopes) et a donné des mesures sur plusieurs étoiles [19]. Il fonctionnait dans le visible avec l'interféromètre SUSI auprès de Narrabri (Australie) [51]. Il est couramment opérationnel dans l'infrarouge proche sur l'instrument GRAVITY au VLTI (mont Paranal, Chili), dont les caractéristiques instrumentales sont données dans l'article de Gillessen et al [52] ; et des résultats d'observations récentes sont donnés dans les articles d'Abuter et al [53], Nowak et al [54].…”
Section: Turbulence Atmosphérique Et Dispersionunclassified
See 1 more Smart Citation
“…Celui-ci a été mis en oeuvre dans l'infrarouge (l'effet de la turbulence et la dispersion y étant moins intenses que dans le visible) au Palomar Testbed Interferometer (à trois télescopes) et a donné des mesures sur plusieurs étoiles [19]. Il fonctionnait dans le visible avec l'interféromètre SUSI auprès de Narrabri (Australie) [51]. Il est couramment opérationnel dans l'infrarouge proche sur l'instrument GRAVITY au VLTI (mont Paranal, Chili), dont les caractéristiques instrumentales sont données dans l'article de Gillessen et al [52] ; et des résultats d'observations récentes sont donnés dans les articles d'Abuter et al [53], Nowak et al [54].…”
Section: Turbulence Atmosphérique Et Dispersionunclassified
“…Si, comme dans bien d'autres interféromètres (ISI [55], SUSI [51], le VLTI [56] et le LBTI [57]) on préfère laisser la ligne à retard dans l'air ambiant, donc au voisinage du sol, il faut calculer non seulement les déplacements qui vont égaliser entre eux ∆ ′ A et −∆ A pour une longueur d'onde donnée de la bande spectrale utilisée, mais encore la dispersion causée sur ces grandeurs par l'air dans les trajets au sol, que l'on suppose à température et pression constante -car, même s'ils ne sont pas sous vide, ils sont au moins protégés grâce à un ensemble de passages aménagés (appelé « le métro » au VLTI [58, p. 191-192]). Avec une ligne à retard ordinaire sur la voie (2) le chromatisme de ∆ ′ A est beaucoup plus grand que celui de −∆ A , donc il faudra compenser cet excès de chromatisme par des dispersions équivalentes avec une lame à faces parallèles compensatrice (habituellement en verre) d'épaisseur e ajustable, mise sur (1) entre A ′ et la sortie de (T 1 ).…”
Section: Compensation De ∆ a Par Une Ligne à Retard Dans L'airunclassified
“…23 Similarly, due to uncertainties in the baseline solutions and the wavelength scale used in the data reduction, the binary separation and position angle measurements obtained with PAVO may have systematic errors not reflected in the uncertainty numbers reported in the table. For most of the PAVO observations, instead of using a more precise approach, 6 optical alignment was carried out with the standard SUSI alignment procedure. The latter approach typically aligns the apertures of the PAVO 2-hole mask with the pivot points of the siderostats to within 2cm.…”
Section: γ Lupimentioning
confidence: 99%
“…Among the approaches, the direct differential phase measurement is the most commonly implemented. [2][3][4][5][6] The direct measurement approach has been extensively discussed in the literature. Instruments that implement this approach are engineered to measure the optical path of the starlight to an accuracy of better than 5nm with a baseline in the regime of 100m in order to attain the required precision.…”
Section: Introductionmentioning
confidence: 99%
“…Reducing fringe tracking residuals below a radian of fringe phase is often seen as a way to achieve long integrations in the presence of detector noise, 1 but measuring fringe phase with a sub-radian accuracy has a much more fundamental application in enabling coherent integration 2 of differential quantities such as closure-phase, wavelength-differential phase 3 and dual fringe packet astrometry. 4,5 Several future interferometer concepts, such as high-contrast imaging in the mid-infrared with VLTI, 6 or the PFI 7 require high accuracy fringe tracking in order to operate. In fact, recent work on the concept of kernel nulling 8 has shown that nulling interferometry contrasts are often proportional to the cube of the fringe tracking residual, and require residuals smaller than 50 nm in order to achieve key high-contrast exoplanet detection goals.…”
Section: Introductionmentioning
confidence: 99%